Persepsi Masyarakat Muslim Terhadap Gerakan Boikot Produk Pro-Israel Sebagai Bentuk Jihad Ekonomi - Sabrina Nufikho Hidayah; Malta Anantyasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted with the aim of finding out how the public, especially Muslims, perceives the pro-Israel product boycott movement which is currently still being carried out massively everywhere. Finding out whether they are participating in this boycott movement, and finding out the perception of the Muslim community regarding the pro-Israel product boycott movement as a form of economic jihad. The many pros and cons of the boycott and not yet discussed in terms of economic jihad are the basis for this study. This study is classified as a descriptive qualitative study with a snowball sampling technique using an open questionnaire to 30 Muslim community informants ranging from generation X, generation Y/Millennials, to Generation Z in Pacitan City, Indonesia. The author uses data analysis techniques, namely interactive analysis techniques. The results of the study show that the majority of Muslims in Pacitan City have a fairly good understanding of the conflict between Palestine and Israel. They also said that the boycott movement of products considered pro-Israel is a good movement to do. Not only that, most of them also follow this movement, and agree that the boycott of pro-Israel products is a form of non-physical struggle in defending the rights of Muslims, especially the Palestinian people in the economic sector which is in line with the concept of economic jihad. However, there is also a small portion of the community who stated that they do not yet understand deeply about this matter.